CONCEPT OF MOBILE MODULAR HELIUM COOLED HIGH TEMPERATURE FAST NUCLEAR REACTOR - IMADA SAMOSIR (NIM : 10208031); Pembimbing: Prof. Dr. Zaki Su'ud, ANDREW
The growth in world industry and population in the 21st century causes the exponential growth of energy demands. Yet, conventional power sources cost efficiency and environmental issues are still not yet resolved to the energy demands growth. The alternative power source that is cheap, environment-friendly, and massive, is the nuclear power. However, nuclear power requires large and complex constructs and capital investments, and the utility is limited. Therefore, the solution is to design a nuclear reactor that works at Fast Breeder Mode for lower fuel enrichment, high pressure and high temperature operation on Brayton thermal cycle for higher thermal efficiency, small dimension, transportable by common means such as railroads, and modular in design. We use SRAC to simulate Modular Gas Cooled Fast Reactor at High Temperature Operation in order to optimize the active core outputs and characteristics, also utilizing lightweight materials to achieve lower reactor weight. Results show that such reactor can be feasibly created with refueling cycle of 15 years, with power output of 220 MW in thermal or 112.3233425 MW in electric, with dimension of 3.9 meter in length and width and 9.2 meter in height, and fuel enrichment of U-235 at 6.25 %, at the total reactor weight of 293.23 tons.